A Study on The Sandwich Generation Differences in Level of Work-Family Conflict and Marital Satisfaction among Working Couple - Devancy Sharinda Mangkey; Karel Karsten Himawan (Psympathic : Jurnal Ilmiah Psikologi, 2023)
Dual-earner couples in the sandwich generation are overcoming unique challenges to their marital satisfaction. Therefore, this study aimed to explore gender differences in work-family conflict and marital satisfaction in dual-earner couples among the sandwich generation. To achieve this, a quantitative mathod comprising 105 participants (Mage = 39.10; SD = 9.842) from Greater Jakarta, was used. The results showed that there was no significant differences between working men and women in the sandwich generation concerning marital satisfaction and work-family conflict. Based on observations, there was no correlation between work-family conflict and marital satisfaction in women. Conversely, a negative correlation existed between marital satisfaction and the number of children, a trend discovered exclusively in men. In conclusion, this study provided information to improve the marriage quality for dual-earner couples and contributed novel perspective to the discourse on marital satisfaction and work-family conflict.